The Effect of Assertiveness Program on Clinical Competence of Intensive Care Units Nurses; A Randomized Clinical Trial - Samira Abbasi; Reza Masoudi; Leili Rabiei; Koroush Shahbazi (Hamadan University of Medical Sciences, 2019)
Introduction: Clinical competence of nurses is an effective factor in ensuring the quality of care in a competitive modern world. Given the vital role of nurses and the weakness of existing assertiveness, this concept as a communication style can play an important role in improving performance and improving the quality of care in tense stressful care settings. The purpose of this study was to determine the effect of the assertiveness program on the clinical competence of nurses in intensive care units. Method: In this clinical trial, 70 nurses of ShahreKord in 2018 were randomly allocated into two groups experimental and control. The experimental group was trained in 6 sessions of ninety minutes, while the control group did not receive the training. Data was collected before, immediately and 3 months after intervention by demographic and CIRN Clinical Competency Questionnaire and analyzed using SPSS 17 with independent t-test, ANOVA with repeated measurement and Chi-square. Results: There was no significant difference between the mean scores of clinical competency between the two groups before intervention, but this difference was significant in the immediately and 3 months after intervention based on independent t-test (P<0.05). ANOVA test with repeated measurement showed a significant difference in the process of changes in mean scores in the three stages of measurement (before, immediately and three months after the intervention) (P<0.001). Conclusion: Assertiveness education leads to increasing the clinical competence of nurses in intensive care units. Therefore, it is suggested to be used in nursing education courses.